2021
DOI: 10.3846/jcem.2021.15852
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis for Rent-Seeking Behavior Supervision of Major Infrastructure Projects Based on Prospect Theory

Abstract: Major infrastructure projects (MIPs) possess significant strategic positions in the national economy and social development. However, recently, the rent-seeking behavior between supervision units and project contractors has intensified in project construction. This paper aims to study the behavior decision-making of stakeholders in rent-seeking behavior supervision system of MIPs. In the complex and uncertain environment of MIPs, game players have cognitive bias and value perception preference. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Stability analysis is commonly used to determine the long-run equilibrium strategy of each participant ( 55 ). In this paper, dynamic differential analysis is used to obtain the equilibrium strategy of the system.…”
Section: Methodsmentioning
confidence: 99%
“…Stability analysis is commonly used to determine the long-run equilibrium strategy of each participant ( 55 ). In this paper, dynamic differential analysis is used to obtain the equilibrium strategy of the system.…”
Section: Methodsmentioning
confidence: 99%
“…From prospect theory, it is known that 0 < α, γ, λ > 1, indicating those decision makers are more sensitive to losses compared to gains. According to existing studies, when α= γ = 0.88, λ = 2.25 is assumed to represent the approximate behavioral preferences of decision makers, the decision influence coefficient θ = 0.69 (Khan et al, 2021;Shen et al, 2021;Lv et al, 2022). According to Marshall and Hirmas' 1:300 principle (Marshall et al, 2018), P 0 = 0.03, and the initial values of other parameters were set as follows…”
Section: Evolutionary Simulation and Analysismentioning
confidence: 99%
“…Then prospect theory and evolutionary game are applied in different scenarios. To study rent-seeking behavior in major infrastructure projects (MIP), (Lv et al, 2022)constructed an evolutionary game model among project owners, supervision units, and project contractors based on prospect theory, studied the strategy selection and stability conditions of game participants, and provided a decision-making basis for major infrastructure…”
Section: Introductionmentioning
confidence: 99%
“…Song et al ( 2021 ) suggested that the interests and costs of users should be taken into account in the decision-making stage after analyzing the tripartite game among users, public sectors and private sectors in user paid PPP projects. Lv et al ( 2021 ) investigated the evolution of concession renegotiation behaviors when the actual flow in PPP transportation project was inconsistent with the expected flow through evolutionary game, which provides decision support for the governance of concession renegotiation behaviors in PPP projects. Loghman et al ( 2022 ) established a mixed-integer programming model consisting of game theory and project schedule to reduce the duration of grand infrastructure projects with a minimum increase in cost.…”
Section: Introductionmentioning
confidence: 99%